HUBUNGAN PENGETAHUAN DAN SIKAP IBU BALITA DENGAN UPAYA PENCEGAHAN STUNTING DI DESA BINTANG WILAYAH KERJA PUSKESMAS BATANG BERUH KECAMATAN SIDIKALANG TAHUN 2023 - Naibaho, Risdiana Melinda; Doloksaribu, Tiurlan Marasima; Silaban, Jojor (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
Stunting is a failure of growth and development that can have an impact on the future of children related to the low quality of human resources, namely low intelligence, increased risk of non-communicable diseases, and stunting in adulthood. Prevention of stunting is much easier than treatment of stunting. Talking about stunting prevention interventions not only for toddlers, but mothers are the main subject by strengthening knowledge and attitudes as an effort to increase understanding of stunting so that a positive attitude will reflect to take action so that stunting reduction is achieved. This research is a quantitative study using a ‘Cross Sectional’ research design. This study aims to determine the relationship between knowledge and attitudes of mothers of toddlers towards stunting prevention efforts. The population in this study were 68 mothers of toddlers. The sampling technique is random sampling and samples that meet the inclusion criteria. The results of the chi square statistical test obtained the results of knowledge p value = 0.001 with stunting prevention efforts as well as the attitude p value = 0.001 there is a close relationship between knowledge and attitude towards stunting prevention efforts. It is hoped that mothers of toddlers can increase knowledge and change mindset attitudes to act to seek information and follow government programmes so that they can make efforts to prevent stunting.